Pengaruh Model Pembelajaran Problem Based Learning Terhadap Hasil Belajar Siswa pada Mata Pelajaran Pendidikan Pancasila Kelas IV di SDN 20 Cakranegara - Yulia Rahmawati; Khairun Nisa; Lalu Hamdian Affandi; Hj. Nurhasanah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Abstract: The ability of learning outcomes of Pancasila education of grade IV students at SDN 20 Cakranegara is still low. This problem is caused because during the learning process the teacher uses a learning method that is still centered on himself such as lectures without any other variations. This study aims to determine the effect of the problem based learning model on student learning outcomes in the Pancasila education subject in grade IV of SDN 20 Cakranegara. This type of research is an experiment with a Quasi Experimental design with a pretest-posttest control group design type. This design has two groups that are selected randomly. The population consists of 25 students in the experimental class and 25 students in the control class, a total of 50 students in grade IV at SDN 20 Cakranegara. The data collection technique is a test. The test is used to measure students' Pancasila education learning outcomes. The instrument requirement test in this study includes a validity test, a reliability test, a discrimination test and a difficulty level test. The data analysis test uses the t-test, but previously a requirement test was carried out in the form of a normality test, the results of the normality test obtained data with a significance value of > 0.05, so it can be concluded that the research data is normally distributed. The results of the pretest and posttest homogeneity tests obtained sig of 0.76 and 0.10, which means > 0.05, so the data is declared homogeneous. The results of the hypothesis test were obtained through the independent sample t-test test, getting sig (2-tailed) 0.001 <0.05, so H0 is rejected and Ha is accepted. So it can be concluded that there is an influence of the problem based learning model on student learning outcomes in the Pancasila education subject at SDN 20 Cakranegara.